Assessing and broadening genetic diversity of a rapeseed germplasm collection - Wu, Jinfeng (Breed Sci, 2014)
Assessing the level of genetic diversity within a germplasm collection contributes to evaluating the potential for its utilization as a gene pool to improve the performance of cultivars. In this study, 45 high-quality simple sequence repeat (SSR) markers were screened and used to estimate the genetic base of a world-wide collection of 248 rapeseed (Brassica napus) inbred lines. For the whole collection, the genetic diversity of A genome was higher than that of C genome. The genetic diversity of C genome for the semi-winter type was the lowest among the different germplasm types. Because B. oleracea is usually used to broaden the genetic diversity of C genome in rapeseed, we evaluated the potential of 25 wild B. oleracea lines. More allelic variations and a higher genetic diversity were observed in B. oleracea than in rapeseed. One B. oleracea line and one oilseed B. rapa line were used to generate a resynthesized Brassica napus line, which was then crossed with six semi-winter rapeseed cultivars to produce 7 F(1) hybrids. Not only the allele introgression but also mutations were observed in the hybrids, resulting in significant improvement of the genetic base.